PENGEMBANGAN BAHAN AJAR MENULIS TEKS PROSEDUR DENGAN MENGGUNAKAN MEDIA BERBASIS APLIKASI ANDROID G-TEKS PRO (GENRE TEKS PROSEDUR) - Dara Fitriana Adinda Agrin; N. Lia Marliana; Reni Nur Eriyani (Jurnal Semantik, 2021)
In the industrial revolution 4.0, learners were a generation very close to the technology touch. Thus, teachers can not only rely on environmentally based media but also be able to use technology-based media that is both attractive, creative and innovative to achieve learning competence. The purpose of this study is to develop the teaching material for writing the procedure text using a media application called G-Teks Pro (Genre Teks Prosedur)  using the research and development method. The application development model is ADDIE (design, development, development, development, development). The study population was SMPN 216 Jakarta class vii of 34 people. Data retrieval comes from observation, interview, and angket. The analysis used is qualitative and quantitative. After research, the pro-text android application was successfully developed and therefore flexible access. Furthermore, the quality of the application is rated highly appropriate/excellent according to the validator average value, which is 85.59%. Each rating is media expert 83.77%, materials expert 85.00%, and Indonesian teacher 88.00%. Later, the student merepons application at trial by giving an excellent assessment of 87.24%. Hence,  G-Teks Pro applications imper on learning that can be used as teaching materials and thus improve writing skills, especially of the procedure text.